Engagement and retention in HIV care in rural Southern U.S. using an All-Payer Claims Database - Jun Tao; Mofan Gu; S. Alexandra Marshall; Jure Baloh; Mike Cima; Cornelius Mabin; Nickolas D. Zaller; Dan Moore; Hannah Parent; Heather Horton; Ira B. Wilson; Amy S. Nunn; et al. (PLoS ONE, 2025)
Access to HIV care is a persistent challenge in rural settings. Arkansas has one of the highest proportions of rural residents in the U.S., yet data on statewide engagement and retention in HIV care are limited. This study used the Arkansas All-Payer Claims Database (APCD), a longitudinal database of medical, pharmacy, and enrollment claims from Medicaid and most commercial insurers, to evaluate the HIV care continuum and spatial access to providers. We identified people living with HIV (PLWH) from 2013–2017 using an algorithm requiring ≥2 HIV diagnosis claims or ≥1 prescription for antiretroviral therapy (ART). Engagement in care was defined as ≥1 CD4 or viral load (VL) test in a calendar year, while retention was defined as ≥2 tests in a year. Geospatial accessibility to HIV care at the county level was assessed using ArcGIS. A total of 5,033 PLWH in Arkansas were identified across the 5-year period. Only 18–21% of this population received CD4 testing and 47–51% received VL testing annually. ART prescription fills ranged from 61–88% annually. HIV testing rates among the broader insured population were also low, particularly in rural counties. There were 92 unique physicians with HIV-related care claims during the study period, equating to approximately 1 provider per 50 PLWH. Spatial access and care engagement were lower in rural counties. Significant gaps exist in HIV care engagement and retention in Arkansas, with notable gender and rural/urban disparities. Targeted interventions are crucial to address these disparities and end the HIV epidemic in the state.